Analisis Kepuasan Kerja Karyawan Baitul Maal wa Tamwil Ditinjau dari Teori Dua Faktor Herzberg - Rahadi, Qisthian; Rozikan, Rozikan (Al Maal: Journal of Islamic Economics and Banking, 2024)
This research uses Herzberg's two-factor theory, namely motivator factors which include the work itself and promotion and hygiene factors which include relationships between co-workers, salary and supervision to measure job satisfaction of BMT UMY, BMT Artha Sejahtera and BMT Al-Mukhlish Yogyakarta employees. This research aims to find out what factors are most dominant in BMT employees and why these factors influence employees as well as the relationship between Herzberg's two-factor theory and BMT employee job satisfaction. This type of research is descriptive qualitative research, The results of this study conclude that job satisfaction among BMT employees is measured using Herzberg's two-factor theory. It can be said that hygiene factors play a full role in BMT employees so that they avoid job dissatisfaction and can create feelings of satisfaction with their work. The conclusion of this research is that the job satisfaction felt by each BMT employee in this case shows that hygiene factors dominate, especially the relationship factor between co-workers